LIVED EXPERIENCES OF COLLEGE STUDENTS IN PANDEMIC ERA: A PHENOMENOLOGY - Jayson B. Busano; Juliet B. Busbus; Joann P. Ladres; Gabrele D. Cubero (EPRA International Journal of Environmental Economics, Commerce and Educational Management (ECEM), 2022)
The coronavirus disease 2019 (COVID-19) brought extraordinary disruptions to educational platforms worldwide. Specifically, this pandemic crisis caused Philippine higher education institutions to abruptly shift to online classes due to the call for continued education despite global health issues. This paper aims to explore and understand the lived experiences of college students while studying during the pandemic. It is used to describe how human beings experience a particular phenomenon. In the study, 14 First-Year college students from the education department were purposely selected to participate. The researcher gathered information from the participants through individual in-depth interviews. It is to attempt to access the thoughts and feelings of study participants. This study revealed seven themes: poor internet connection, loss of interest in learning, difficulty in learning; focusing on life goals, praying to God; difficulty in the new normal education, and new normal education has positive and negative sides. Interestingly, the study found that poor internet connection was the students’ major problem in online learning. Consequently, college students’ experiences in online classes should be understood and provide a lending ear to be heard and a voice for building a pedagogy of understanding about their learning journey in this pandemic crisis. Nevertheless, the CHED and the government must provide resources that would help the student’s online class, enough resources, and support for the holistic development of the learner’s educational needs.